Comfort Need of Hospitalised Patients With Covid‐19 During Isolation Precaution: A Qualitative Study - Chiyar Edison; Agung Waluyo; Sri Yona; Tris Eryando (Wiley, 2024)
ABSTRACT Aim This study aimed to explore the experiences of hospitalised patients with Covid‐19 in terms of the meeting of their comfort needs and the source of discomfort during isolation precautions. Design Qualitative descriptive phenomenological approach was applied in this study. Methods There were 16 hospitalised patients with Covid‐19 and 11 nurses who were thoroughly interviewed. Content analysis was conducted to examine the data of the interviews and then managed using Atlas ti‐9 software. Results Five central themes were identified that describe the comfort needs and the source of discomfort, as follows: (1) nursing professionalism; (2) physical discomfort; (3) psychological responses; (4) poor sleep quality; and (5) spiritual adaptations. Public Contribution The study promoted further explanation about comfort need in patients with Covid‐19 in isolation room. This study also highlighted that nursing care played a pivotal part in assisting patients to reach their highest comfort level.